Identifikasi Permasalahan Infrastruktur Drainase di Kampus Universitas Hasanuddin Tamalanrea, Kota Makassar - Shohifah Shaf; Annisya Alifvia Soehartono; Yashinta Kumala Dewi Sutopo; Muhammad Fathien Azmy (Department of Urban and Regional Planning, Faculty of Engineering, University of Hasanuddin, 2021)
The Unhas Tamalanrea campus is an educational area which has an area of 220 hectares, one of the problems that exist when the intensity of rain is high enough in the area, namely the occurrence of inundation and flooding on several roads so it is necessary to find causes and solutions to these problems. The purpose of this study was to determine the problem of drainage infrastructure in the Unhas area. This research took place from November 2020 to April 2021. This research is located in the Hasanuddin University Area, Tamalanrea Campus, which is located in Tamalanrea District, Makassar City. Types of secondary data are the number of Unhas Tamalanrea campus communities, the volume of dirty water per person based on the number of communities in Unhas Tamalanrea and PERMEN PU RI No.12/PRT/M/2014 with data collection methods, namely literature, theory, and NSPK studies. The type of primary data is the existing condition of the drainage network at the Unhas Tamalanrea campus, with data collection methods namely surveys or field observations. The data analysis technique used is a comparative analysis, which is to compare the ideal or proper drainage infrastructure with the existing conditions of the research location. Based on the results of the study, there is a drainage infrastructure that is classified as a tertiary drainage channel and then leads to a secondary drainage channel on Polytechnic Street and empties into the Tallo River as a primary drainage channel that is well connected. The quality of the drainage infrastructure is not good, seen from the dimension of the drainage construction that is not wide enough and the drainage network where sedimentation occurs due to lack of maintenance.